ANALYSIS RISK AND RETURN OF CROPS PORTFOLIO - Wibowo, Rulianda Purnomo; Pebriyani, Dian (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Agricultural sector is exposed to risk especially risk in crop price or production volatility. The cropping pattern or mixed cropping is a diversification strategy which is considered as an approach to reduce the risk in agriculture farming. This research was conducted to analyze the combination of two plant types, namely vegetable crops and food crops. Portfolio combine longbean and spinach as vegetable crop portfolio and paddy and corn as food crop portfolio. The risk analysis method is used to calculate expected return, standard deviation and coefficient variation. This research also analyzes the choice of portfolio based on preference using Stochastic Efficiency with Respect to A Fuction (SERF). The results showed that with the aim of reducing the risks from farming, combination of spinach with longbean and paddy with corn can reduce risks and provide greater income. Moreover, at various levels of risk preference, the vegetable portfolio is more preferred than food crops portfolio. This study result implies a potential development for vegetable crops vertical farming in Medan.